Konsep Sir dan Sirrul Sir al-Ghazali dalam Kitab Sirāj al-Ṭālibīn Karya Syekh Ihsan Jampes serta Relevansinya terhadap Kesehatan Mental - Moch. Rizqi Fadhilah; M. Syauqi Fadhillah; Ahmad Haromaini; Aslihatul Rahmawati; Rosidi Rosidi (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2026)
This study was motivated by the limited scholarly attention devoted to linking the inner dimensions of classical Islamic mysticism, particularly qalb, lathifah ruhaniyyah, Sir, and Sirrul Sir, with contemporary psychology of religion and mental health. It aims to analyze these concepts in the thought of Imam al-Ghazali as elaborated by Shaykh Ihsan Jampes in Sirāj al-Ṭālibīn and to examine their relevance to psychospiritual resilience, positive religious coping, and mental health. Employing a qualitative descriptive library research approach with content analysis, this study examines primary sources, namely Ihyā’ ‘Ulūm al-Dīn and Sirāj al-Ṭālibīn, supported by contemporary scholarly literature. The findings reveal that qalb represents the lathifah rabbaniyyah as the center of human spiritual consciousness, while Sir and Sirrul Sir describe deeper spiritual dimensions that guide individuals toward self-awareness, meaning-making, and complete surrender to Allah. Furthermore, the stages of Sir al-‘Ilm, Sir al-Hāl, and Sir al-Haqīqah illustrate a process of spiritual development that cultivates humility, meaning-making, and tawakkul. Overall, this study concludes that these concepts provide a relevant conceptual foundation for strengthening psychospiritual resilience, positive religious coping, and mental health in addressing contemporary psychological challenges.